Effects of serotonin and norepinephrine reuptake inhibitors on depressive- and impulsive-like behaviors and on monoamine transmission in experimental temporal lobe epilepsy - Kumar, Udaya (Epilepsia, 2016)
OBJECTIVE: Examine therapeutic potential of a selective serotonin reuptake inhibitor (SSRI) and a norepinephrine reuptake inhibitor (NERI) in an animal model of comorbidity between epilepsy, depression-like, and impulsive-like impairments. METHODS: Epilepsy was induced in male Wistar rats by LiCl and pilocarpine. An SSRI fluoxetine (FLX), and a NERI reboxetine (RBX) were administered either alone or as a combination over one week. Depressive-like and impulsive-like behaviors were examined using forced swim test. Fast scan cyclic voltammetry was used to analyze serotonergic transmission in the raphe nucleus (RN)-prefrontal cortex (PFC) pathway, and noradrenergic transmission in locus coeruleus (LC)-PFC, and LC-RN projections. Monoamine levels in PFC were measured using high performance liquid chromatography. Functional capacities of 5-HT1A receptors and α2A adrenoreceptors in PFC were analyzed by autoradiography. RESULTS: Epileptic rats showed behavioral signs of depression and hyper-impulsivity, suppressed serotonergic and noradrenergic tones, decreased levels of serotonin (5-HT) and norepinephrine (NE); 5-HT1A receptor and α2A adrenoreceptors functions remained intact. FLX failed to improve behavioral deficits, but effectively raised 5-HT level and marginally improved RN-PFC serotonergic transmission. RBX reversed impulsive-like behavior, normalized content of NE and noradrenergic tone in LC-PFC and LC-RN. FLX-RBX combination fully reversed depressive-like behavior, and normalized RN-PFC serotonergic transmission. None of the treatment modified the function of 5-HT and NE receptors. SIGNIFICANCE: Depressive- and impulsive-like behaviors in the pilocarpine model of epilepsy stem respectively from dysfunctions of serotonergic and noradrenergic ascending pathways. At the same time, epilepsy-associated depression is SSRI-resistant. The finding that an SSRI-NERI combination exerts antidepressant effect, along with RBX-induced improvement of LC-RN noradrenergic transmission point towards the involvement of LC-RN noradrenergic input in enabling therapeutic potential of FLX. Medications that improve serotonergic and noradrenergic transmission, such as serotonin-norepinephrine reuptake inhibitors may be effective in treating epilepsy-associated SSRI-resistant depression, as well as concurrent depression and ADHD.